EDUKASI PENTINGNYA PEMERIKSAAN ANTENATAL CARE UNTUK SKRINNING RESIKO TINGGI KEHAMILAN DI DESA WOWONDA KABUPATEN KEPULAUAN TANIMBAR - Saragih, Kristiova Masnita; Arvicha Fauziah; Kasmiati, Kasmiati (Bajang Institute, 2025)
The partner in this community service program is Wowonda Village, with the aim of providing health knowledge to pregnant women about the importance of antenatal care examinations for high-risk pregnancy screening in Wowonda Village. This is based on the many cases of pregnant women who do not routinely carry out antenatal care (ANC), carry out antenatal care (ANC) only when approaching delivery 83.3% and some do not carry out antenatal care (ANC) during pregnancy 8.33%, and most 41.66% of pregnant women experience high-risk pregnancy anemia in their pregnancies. The target output is to increase the knowledge of pregnant women and cadres about the importance of antenatal care examinations for high-risk pregnancy screening. To achieve this goal, the community service team uses a chronological strategy, with a sequence of implementation starting from a pre-test, providing educational materials with lectures, discussions and continuing with knowledge evaluation.